Guide :

Algebra 1 equation on my way to school needs help now

## Research, Knowledge and Information :

Can someone please help me solve 3? Thank you!! (: Download png. 2. ... The 10 comes from the amount of letters and the 2 comes from the 2 As and the 3 comes from the ...

### Mathway | Math Problem Solver

Please try again. Please ... you must allow Mathway to ... Visa and MasterCard security codes are located on the back of card and are typically a separate group of 3 ...

... (2x + 4) = 6 * 2x + 6 * 4 = 12x + 24 The equation now looks like this 12x + 24 = 10x + 24 + 2x Notice ... Please help me solve: 6(2x+4) ... Please explain why or ...

### PLEASE HELP :3 Solve 2x + 5y = −13 3x − 4y = −8... - OpenStudy

PLEASE HELP :3 Solve 2x + 5y = −13 3x − 4y = −8 (4, 1) (−4, 1) (4, −1) (−4, −1) Mathematics ...

### Math Help 1) Solve the triangle. A = 46, a = 31, b = 27 a) B ...

Answer to Math Help 1) Solve the triangle. A = 46, a = 31, ... Solve the triangle. A = 54°, b = 11, c = 8 a) ... Can you please help me with my assignment. please ...

## Suggested Questions And Answer :

### solve x²+7x+12= 0

solve x²+7x+12= 0 I need to know how to work it out - please help!!!!! x² + 7x + 12 = 0 We need to find factors of 12 that add up to 7. They must be 3 and 4 (x + 3)(x + 4) = 0 One, or both, of those factors on the left must equal zero. (Multiplying by zero produces a zero result.) Set each one to zero and solve for x. (x + 3) = 0 x = -3 (x + 4) = 0 x = -4 Check both answers using the original equation. x² + 7x + 12 = 0 -3² + 7(-3) + 12 = 0 9 - 21 + 12 = 0 0 = 0 x² + 7x + 12 = 0 -4² + 7(-4) + 12 = 0 16 - 28 + 12 = 0 0 = 0 So, x = -3 and x = -4 are solutions. If you graph this equation, you will get a parabola that crosses the x axis at two points: (-3, 0) and (-4, 0)

### solve y= 5x+2, x=6-3y. this is systems of equations :)

Problem: solve y= 5x+2, x=6-3y. this is systems of equations :) please help me l0l 1) y = 5x + 2 2) x = 6 - 3y Substitute the value of y, from equation 1, into equation 2. x = 6 - 3y x = 6 - 3(5x + 2) x = 6 - 15x - 6 x + 15x = 6 - 15x - 6 + 15x 16x = 6 - 6 16x = 0 x = 0 Use that to solve for y. y = 5x + 2 y = 5(0) + 2 y = 0 + 2 y = 2 Check. x = 6 - 3y 0 = 6 - 3(2) 0 = 6 - 6 0 = 0 Answer: x = 0, y = 2

### how can you get the answer 7 while only using the number 2,0,1, and 2?

My there brethren and standing hear today, it just because what DR. UWA has done me for me with problem of my husband. Contact him at: [email protected]. I am using this opportunity to share the testimony of what DR. UWA has done, he help me in such away that I didn’t no now to thank him. Been through **** and pain, looking for a good and real spell caster who can help me get my husband back. I have been scammed my many spell cater, by some who claimed to be real spell casters. Until I found the real and great spell caster is name is Dr.UWA who helped me, and solved all my problems concerning my husband who left me since 3 years ago. and after that i also took my friend along, who was also having the same problem who help me to bring my husband, who left her since 2 year ago he help me with out no payment DR.UWA is a great doctor, whenever you are in any problem relationship please contact him at [email protected] It took me a very long period of time, before I could get this real and great spell caster. So right now is here, and the best for you to solve your problems please contact [email protected]

### Help understanding the quadratic equation

if the quadratic eqn is ax^2 + bx+c = 0 you can use the formula -a +/- sqrt(b^2-4ac) / (2a) in your case, all can be factored 1. (x-5)(x+1) = 0 2. (z-5)(z+3) = 0 3. (y-3)(y+1) = 0 4. (r+5)(r-1) = 0

x-3=-sqrt(25-12x)... (x-3)^2=(25-12x) x^2 -6x +9 -25+12x=0 x^2 +6x -16=0 (x-2)(x+8)=0 #### go bak tu top...(25-12x) gotta be >=0, so x gotta be < 25/12...2.083333333... ok, x=2 & x=-8 pass

please explain 5sinx+5=0 i came across this problem studying level 5 mathematics and was unsure how to solve it please help It is solved the way any algebra problem is solved. Add, subtract, multiply and divide as necessary to get the x term alone on the left side of the equation. 5 sinx  + 5 = 0 5 sinx + 5 - 5 = 0 - 5 5 sinx = -5 (5 sinx) / 5 = -5 / 5 sin x = -1 At this point, we don't have x, we have the sine of x. By using the inverse sin function, we can find what x is. x = arcsine -1 x = 90 degrees

### Guys can you help me solve these following equations

This should help: Simplifying 3p + -1 = 5(p + -1) + -2(7 + -2p) Reorder the terms: -1 + 3p = 5(p + -1) + -2(7 + -2p) Reorder the terms: -1 + 3p = 5(-1 + p) + -2(7 + -2p) -1 + 3p = (-1 * 5 + p * 5) + -2(7 + -2p) -1 + 3p = (-5 + 5p) + -2(7 + -2p) -1 + 3p = -5 + 5p + (7 * -2 + -2p * -2) -1 + 3p = -5 + 5p + (-14 + 4p) Reorder the terms: -1 + 3p = -5 + -14 + 5p + 4p Combine like terms: -5 + -14 = -19 -1 + 3p = -19 + 5p + 4p Combine like terms: 5p + 4p = 9p -1 + 3p = -19 + 9p Solving -1 + 3p = -19 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -1 + 3p + -9p = -19 + 9p + -9p Combine like terms: 3p + -9p = -6p -1 + -6p = -19 + 9p + -9p Combine like terms: 9p + -9p = 0 -1 + -6p = -19 + 0 -1 + -6p = -19 Add '1' to each side of the equation. -1 + 1 + -6p = -19 + 1 Combine like terms: -1 + 1 = 0 0 + -6p = -19 + 1 -6p = -19 + 1 Combine like terms: -19 + 1 = -18 -6p = -18 Divide each side by '-6'. p = 3 Simplifying p = 3

(yx-3)(-12x +7) =-72x^2 +36x +42x -21 =-72x^2 +78x -21 if set it=0, get zeroes...(x-0.5)*(x-0.583333333)=0

26r-2=3r^2. The standard quadratic form is ax^2+bx+c=0, where x is the unknown and a, b and c are numbers. The unknown is r in this problem, so let's put the equation into quadratic form: 3r^2-26r+2=0. Note the sign changes as terms are transferred from one side to another, and also note that, in order to preserve the 3r^2 on the right I've brought all the terms over to the right to bring them all together. In doing so, which would have made the equation 0=3r^2-26r+2, I've moved the equals and zero over to the right to get it into quadratic form. I can do this because if A=B then it's true that B=A. This equation doesn't factorise, so we need the formula to solve it: r=(26+sqrt(26^2-4*3*2))/6 (this is the quadratic formula x=(-b+sqrt(b^2-4ac))/2a). So r=(26+sqrt(676-24))/6=(26+sqrt(652))/6=8.589 or 0.0776.

me assume that stuf shood be . . . d=3k/ (k-8p) . . . d(k-8p)=3k . . . dk -8pd -3k=0 . . k(d-3)-8pd=0 . . . k(d-3)=8pd . . . k=8pd/(d-3)